(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
As a result of the entry of multinationals companies in Iraq for investing in the joint projects through conducting agreements and contracts for work on important and strategic projects to get the necessary funds and various experiences which characterize the foreign participant sides that Iraq currently needs them and because of the non-applying the accounting processing stipulated in the unified accounting system in addition to the absence of a local accounting bases as well as the default of the participant contracts on indicating the accounting methods about those projects which are considered one of the bases that enables auditors in the public sector to depend on it, thus the research paper deals with studying and rectifying the current accounting processing in the State Company for Foodstuffs Trading according to the international accounting criterion No.(31) concerning the investment in the joint projects as well as setting up a proposed accounting framework about the investments in the Joint projects.